A Peer-to-Peer Suicide Prevention Workshop for Medical Students - Alyssa Hjelvik; Alyssa Eldridge; Megan Furnari; Hannah Hoeflich; Jason I. Chen; Brandon Roth; Whitney Black (Association of American Medical Colleges, 2022)
Introduction An estimated 11% of medical students experience suicidal ideation during medical school. Many medical schools teach students how to intervene on behalf of patients experiencing suicidal ideation, but no curriculum in MedEdPORTAL teaches students how to intervene on behalf of peers. Methods The authors designed, implemented, and evaluated a 2-hour workshop to equip medical students with skills and resources to intervene on behalf of a peer in crisis. This workshop comprised a peer-led didactic session and small-group sessions with role-plays and a guided debrief. The resource included a slide deck for the didactic session, a facilitator guide for the small-group session, a student handout with role-plays and self-evaluation questions, and the pre-/postsurvey. Results This workshop was conducted with cohorts of first- and second-year medical students (n = 273) in October and November 2019. Pre-/postsurveys showed the greatest improvements in suicide prevention knowledge (self-rated) and the confidence in and likelihood of asking peers about suicide. Discussion Student feedback indicated that the most valuable parts of the workshop were the peer-led nature of the didactic session, the perspective of a peer's lived experience, and the role-plays. Opportunities for improvement included the scheduling of the session, the potentially triggering nature of the role-play exercises, and the importance of enabling students to opt out discreetly. A version of this workshop is now a permanent part of the first-year curriculum at our institution.